2020
DOI: 10.1186/s12931-020-1325-2
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor agonist protects against acute lung injury induced by ventilator through up-regulation of IL-10 production

Abstract: Background: It is well known that ventilation with high volume or pressure may damage healthy lungs or worsen injured lungs. Melatonin has been reported to be effective in animal models of acute lung injury. Melatonin exerts its beneficial effects by acting as a direct antioxidant and via melatonin receptor activation. However, it is not clear whether melatonin receptor agonist has a protective effect in ventilator-induced lung injury (VILI). Therefore, in this study, we determined whether ramelteon (a melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 53 publications
1
47
0
3
Order By: Relevance
“…For instance, in a murine model, melatonin increased the level of the anti-inflammatory IL-10, along with improved oxygenation and reduced histological damage to the lungs [37]. Furthermore, a recent study using ramelteon, the melatoninergic agonist, in lung-injured rats revealed strong reductions in oxidative markers, reduced edema, neutrophil infiltration, the induction of apoptosis, decreased NF-κB activation and iNOS expression, and lower levels of TNFα, IL-1β, and IL-6 [38]. It should also be pointed out that the practical problem in patients with severe COVID-19 concerns the reduction of pulmonary gas exchange due to surfactant impairments by lipid peroxidation caused by infiltrating neutrophils.…”
Section: Melatonin and Its Anti-inflammatory And Anti-oxidative Propementioning
confidence: 93%
“…For instance, in a murine model, melatonin increased the level of the anti-inflammatory IL-10, along with improved oxygenation and reduced histological damage to the lungs [37]. Furthermore, a recent study using ramelteon, the melatoninergic agonist, in lung-injured rats revealed strong reductions in oxidative markers, reduced edema, neutrophil infiltration, the induction of apoptosis, decreased NF-κB activation and iNOS expression, and lower levels of TNFα, IL-1β, and IL-6 [38]. It should also be pointed out that the practical problem in patients with severe COVID-19 concerns the reduction of pulmonary gas exchange due to surfactant impairments by lipid peroxidation caused by infiltrating neutrophils.…”
Section: Melatonin and Its Anti-inflammatory And Anti-oxidative Propementioning
confidence: 93%
“…73,74 Furthermore, melatonin is protective against ventilator-induced lung injury in animal models. 75,76 Studies in animals and humans have found beneficial effects of melatonin against serious viral infections, including herpes, HIV/AIDS, influenza A-H1N1, West Nile virus, coxsackievirus (the virus that Witek-Janusek et al 41 Qin et al 32 2.911 2.722 IL-6 -0.386 -0.571…”
Section: Anti-inflammatory Effects Associated With Meditation and Yogmentioning
confidence: 99%
“…It is noteworthy that, based on its anti-inflammatory, antioxidative and immune-enhancing features, a putative effect of melatonin in alleviating infection-induced acute respiratory distress has also been proposed [4]. In animal models, this natural hormone has been shown to improve acute lung injury by acting as a direct antioxidant and via melatonin receptor activation.…”
mentioning
confidence: 99%